Aplikasi Presensi Siswa Menggunakan Kode QR (QR Code) di SMK PGRI 28 Jakarta Timur - Bay Haqi; Jonser Sinaga (Ikatan Ahli Informatika Indonesia, 2018)
So far, students' attendance system in schools is still dominated by manual, which is presenting students by taking notes on the paper which will be recaptured from each student attendance data. Since the recap of attendee data manually performed also affects information about the present recapitulation is still limited to the school side only. Teachers may also experience the risk of missing student attendance data that is sometimes tucked away with other files. To help overcome the problem, designed a student presence application system using QR code based on android in SMK PGRI 28 Jakarta. With this application the teacher can do student presences through the QR code printed on the student card using the android smartphone as a QR code reader, so the teacher no longer need to record student presences manually. So the teacher can minimize the risk of data loss of student presences that usually tucked with other files, after which the student presence data can be processed and direkap by the school.